Trust responsiveness and beliefs - Guerra, G; Zizzo, D (University of Oxford, 2002)
Trust responsiveness is the tendency to fulfill trust because you believe that it has been placed on you. The experiment presented in this paper uses two simple trust games to measure directly or indirectly the robustness of trust responsiveness in three conditions: when beliefs are elicited and a summary of these beliefs is transmitted; when beliefs are elicited but not transmitted, when beliefs are not elicited. Insofar as we can tell, trust responsiveness is robust to our belief manipulations: this strengthens the case for the real-world significance of trust responsiveness. Shame provides a possible explanation for unexpected trusters' choices.